The effects of responsive and prpactive market orientation on new product success - Soyaltın, Tuğçe Ezgi; Özer, Alper; Korkmaz, Sezer (My University, 2019)
This study seeks to draw the importance of the process of producing new product in firms of universities’ technoparks. Additionally, the purpose of this empirical study is to show that proactive and responsive market orientation have a significant effects on new product success. The paper designed a mail-survey that was sent to marketing managers, sales managers and general managers of small, medium and large scale enterprises in universities’ technoparks, which resulted in 207 usable surveys. Data were analysed using simple and multiple regression analysis. The results show that proactive and responsive market orientation have a positive effect on innovation orientation; the most important finding is that the responsive market orientation is higher than proactive market orientation. Secondly, innovation orientation is another result that has a strong influence on new product success. Finally, when the mediation effect of innovation orientation has been examined on the relationship between proactive and responsive market orientation and new product success, the consequence is that proactive and responsive market orientation has partly mediated effect to new product success. However, the effect of responsive market orientation has been observed as higher than proactive market orientation.
Keywords: Proactive Market Orientation; Responsive Market Orientation; Innovation; New Product Success